Implikasi Neoplatonisme dalam Pemikiran Islam dan Penelusuran Epistemologis Paham Pluralisme - Iswahyudi, Iswahyudi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
There have been a few number of studies, which epistemologically discuss the idea of pluralism and its relation to philosophy. The existing studies on pluralism put greater emphasis on the interpretation of the Quran than its epistemological aspect, particularly the epistemology of Neo-Platonism. Neo-Platonism is a school developed by Plotinus (d. 270) and Porphyry (d. 303) from Alexandria. Plotinus promulgated the idea of The One and the many. The relation of The One and the many is an emanational relation and entrustment. The consequence of this relation is that the many are representation of The One. The author finds that Islamic thoughts, mainly Islamic philosophy, sufism, and Islamic theology have been inevitably influenced by Neo-Platonism?s idea. As the result, those three disciplines highlight the importance of pluralism, which emphasizes wisdom of life. The wisdom of life is a fruit of Islamic thoughts which are shaded with high eclecticism. Such eclecticism has been characterized with an abductive source of knowledge, i.e. an abstraction from various sources to develop what so-called a non-distinctive oppositional knowledge.